Pengaruh Love of Money, Ethical Sensitivity dan Moral Reasoning Pada Perilaku Etis yang dimoderasi Gender - Emerentiana Ayu N.A.R.Roy; Ni Made Dwi Ratnadi (Journal Of Business, Finance, and Economics (JBFE), 2022)
The many problems concerning unethical conduct have had an impact, certainly considered one among that's lowering public consider in numerous professions. The studies objectives to decide the impact of love of money, ethical sensitivity, moral reasoning with gender as a moderator on moral conduct. Data became accrued via way of means of dispensing questionnaires to college students of the FEB Unud accounting undergraduate program. Samples had been taken via way of means of simple random sampling technique in order that 156 respondents had been obtained. The evaluation approach makes use of Moderated Regression Analysis. The research results indicate that love of money, ethical sensitivity, moral reasoning have a positive effect on the ethical behavior of accounting students. Furthermore, this research indicates that gender weakens the effect of love of money on students' ethical behavior, which means it can moderate, but not moderate the effect of ethical sensitivity and moral reasoning.